Economic impact assessment of highly pathogenic avain influenza on the poultry industry in Ghana - Akunzule, A.N. (Animo Repository, 2009)
This paper estimates the economic costs of Highly Pathogenic Avian Influenza (HPAI) to the poultry industry at the farm and sub-sector levels, and examines the benefits of controlling and preventing the spread of HPAI in Ghana. The scare in 2006 and outbreaks in 2007 have affected consumption of poultry products such as chicken meat and eggs, which sharply dropped by 51% and 64%, respectively. Economic losses due to the HPAI threat, and outbreaks to rural and commercial poultry producers, including those of egg and live bird sellers, have been estimated at US$26.3 million. These losses are due to the destruction of infected eggs and day-old chicks and a drop in market prices (of up to 25%) of day-old chicks and eggs. A total of 40,727 birds from 35 farms died due to HPAI, of which 33% died naturally of the disease and 66% were culled. The Ghanan government spent US$160,000 in compensation paid to producers of culled birds; expenditures for containment of the disease at source and control measures to minimize risk of HPAI such as depopulation, decontamination. A ban on movement of poultry products between 2006 and 2007 amounted to US$ 4.3 million. These control measures eventually prevented the country losing 99.88% of its poultry stock, avoided economic losses valued at US$ 416 million.